(untitled) (The Peerian Journal, 2025)
Acute intestinal obstruction (acute intestinal obstruction, ileus, acute ileus) is a condition that develops with impaired passage of intestinal contents. Among acute surgical diseases of the abdominal organs, acute intestinal obstruction accounts for 3.5–9%. Intestinal obstruction most often occurs between the ages of 20 and 40. It is more common in men than in women. During summer and autumn (July–October), the number of patients with acute intestinal obstruction is higher, since during this period plant foods contain more fiber, leading to increased intestinal strain.